Genetic Characterization of West Nile Virus Lineage 2, Greece, 2010 - Papa, Anna; Bakonyi, Tamás; Xanthopoulou, Kyriaki; Vázquez, Ana; Tenorio, Antonio; Nowotny, Norbert (Emerging infectious diseases, 2011)
We conducted a complete genome analysis of a West Nile virus detected in Culex pipiens mosquitoes during a severe outbreak of human West Nile disease in Greece 2010. The virus showed closest genetic relationship to the lineage 2 strain that emerged in Hungary in 2004; increased virulence may be associated with amino acid substitution H249P.